Biomonitoring of prenatal analgesic intake and correlation with infantile anti‐aeroallergens IgE. Issue 6 (13th April 2016) - Hoeke, H.; Roeder, S.; Mueller, A.; Bertsche, T.; Borte, M.; Rolle‐Kampczyk, U.; von Bergen, M.; Wissenbach, D. K.
Abstract: An association between prenatal acetaminophen or ibuprofen intake and an increased risk of asthma and increased IgE level in children is discussed in various epidemiological studies. Although the molecular mechanistic link is still unknown, the question whether or not acetaminophen and/or ibuprofen are safe pain medications during pregnancy arose. In this study, we associate maternal acetaminophen and ibuprofen intake during pregnancy and breastfeeding to infantile asthma phenotypes and elevated IgE level. Therefore, we analysed questionnaires from a local mother–child cohort and monitored drug intake by LC‐MS biomonitoring in urine. No association was found between drug intake and any analysed health outcome using questionnaire data. For the information obtained from biomonitoring, no association was found for ibuprofen and acetaminophen intakes during breastfeeding. However, an association between prenatal acetaminophen intake and increased infantile IgEs related to aeroallergens was statistically detected, but not for asthma phenotypes.